Temperature rise in the pulp chamber during different stripping procedures - An in vitro study - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2007)
Objective: To measure the temperature changes in the pulp chamber when different stripping procedures were used without any type of coolant. Materials and Methods: Ninety intact, freshly extracted human teeth were used in this study. The teeth were separated into nine groups of 10 teeth each. Mesial and distal sides of the teeth were used separately. The stripping procedures were performed on three different tooth groups (incisor, canine, premolar) with a metal handheld stripper, perforated stripping disk, or tungsten carbide bur. A J-type thermocouple wire was positioned in the center of the pulp chamber and was connected to a data logger during application of stripping procedures. The results were analyzed by analysis of variance (ANOVA) and the Duncan test. Results: Two-factor ANOVA revealed significant interaction between the stripping procedure and the tooth type (P = .000). The results of this study demonstrate that tungsten carbide burs used on mandibular incisors had the highest temperature variation (AT) values, which exceeded the critical level (5.5 degrees C), and this was significantly higher than those of the other stripping procedures (triangle T: 5.63 +/- 1.73 degrees C). On the other hand, six of the nine groups also produced temperature increases above the critical level (5.5 degrees C) for some of the specimens. Conclusions: Frictional heat is a common side effect of stripping procedures, and appropriate measures (ie, cooling application) should be taken particularly for high-speed hand-piece stripping of mandibular incisors.
Keywords: stripping; temperature; pulp chamber; thermocouple; INTRAPULPAL TEMPERATURE; TOOTH; POLYMERIZATION; INCREASE